Adsorption type fluorine removal agent as well as preparation method and application thereof
By preparing modified polyaluminum magnesium lanthanum particles, the existing adsorption type fluorine remover has small adsorption capacity, high processing cost, inconvenient use and difficult regeneration, and has achieved efficient fluorine removal and environmentally friendly and safe adsorption type fluorine remover.
Patent Information
- Application Number
- CN202411909878.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing adsorption-type fluorine-removing agents have problems such as small adsorption capacity, high treatment cost, inconvenient use, and difficult regeneration, and may cause secondary pollution.
By preparing a modified polyaluminum magnesium lanthanum granules, using materials such as sodium silicate, water-soluble chitosan, aluminum salt, magnesium salt, lanthanum salt and sodium carbonate, the adsorption-type fluoride removal agent with multiple functions is formed after stirring, soaking, rinsing and vacuum freeze-drying.
It has achieved efficient fluorine removal, with fluorine removal below 0.2ppm, the adsorption capacity can reach 480mg/g, and the regeneration is simple, the regeneration efficiency can reach more than 96%, and the material is environmentally friendly and safe.
Smart Images

Figure BDA0005205376850000071 
Figure BDA0005205376850000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorine-containing wastewater treatment, and specifically relates to an adsorption-type defluorinating agent, a preparation method and use thereof. Background Art
[0002] Endemic fluorosis is an endemic disease that seriously endangers human health, mainly caused by drinking high-fluoride water. How to remove fluoride efficiently and economically has long been an important issue in the fields of environmental protection and public health. Existing fluoride removal technologies mainly include controlling fluoride pollution from the source, chemical precipitation removal, adsorption removal, etc. Among them, adsorption defluoridation agents have attracted much attention due to their simple operation and significant effects. However, traditional adsorption materials such as activated alumina, bone charcoal, serpentine and hydroxyapatite have problems such as small adsorption capacity, high processing costs, inconvenient use, and difficult regeneration, and may even cause secondary pollution.
[0003] Therefore, it is particularly urgent to develop an adsorption-type defluorination agent that is easy to use, efficient and regenerable. Summary of the invention
[0004] The purpose of the present invention is to provide an adsorption type defluorination agent and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing an adsorption-type defluorinating agent comprises the following steps:
[0007] (1) Slowly add sodium silicate solution to the hydrochloric acid aqueous solution under stirring to control the pH value to 3-5.
[0008] (2) Gradually add polyhydroxy polymer organic matter, stir to dissolve, and react for 1 to 3 hours to obtain modified polysilicic acid.
[0009] (3) Add a water-soluble dispersant to the modified polysilicate, and then gradually add aluminum salt, magnesium salt, and lanthanum salt, and stir well to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution.
[0010] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into the sodium carbonate solution and soak for 12 to 24 hours.
[0011] (5) washing with pure water, controlling the surface moisture, first placing it in the freezer layer of a refrigerator for pre-freezing, and then placing it in a vacuum freeze dryer for freeze-drying, thereby obtaining adsorption-type defluorination agent modified polysilicic acid aluminum magnesium lanthanum particles.
[0012] Wherein, in step (1), the mass fraction of the hydrochloric acid aqueous solution is 10% to 25%, preferably 20%.
[0013] Wherein, in step (1), the concentration of the sodium silicate solution is 0.3-1 mol / L, preferably 0.5 mol / L.
[0014] Wherein, in the step (2), the polyhydroxy high molecular organic matter is one or more of water-soluble chitosan, sodium carboxymethyl cellulose, sodium alginate, pectin, and polyvinyl alcohol, preferably water-soluble chitosan, with a deacetylation degree of ≥85%.
[0015] Wherein, in the step (2), the addition amount of the polyhydroxy polymer organic matter is 0.5% to 3%, preferably 2%; and the reaction time is preferably 2h.
[0016] Wherein, in the step (3), the dispersant is one or more of polyethylene glycol, lignin sulfonate, polyethylene imine, and dodecyl dimethyl betaine, preferably polyethylene glycol (average molecular weight of 400 to 4000), and more preferably polyethylene glycol (average molecular weight of 600).
[0017] Wherein, in the step (3), the amount of dispersant added is 0.2% to 2%, preferably 1.2%.
[0018] Wherein, in step (3), n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2.5:0.5~1.5:0.3~0.8, preferably n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2:1~1.5:0.5~0.8, more preferably n (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8.
[0019] Wherein, in the step (4), the mass concentration of sodium carbonate is 10% to 25%, preferably 20%; and the soaking time is preferably 24 hours.
[0020] Wherein, in the step (5), the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 12 to 24 hours.
[0021] Experimental studies of the present invention show that the higher the deacetylation degree of chitosan, the better the water solubility and the lower the viscosity; at the same time, the water-soluble chitosan contains a large number of hydroxyl and amino groups, is positively charged, and can form a cross-linked network with negatively charged silicate compounds through electrostatic interaction and hydrogen bonding; then metal ions are added in the presence of a dispersant PEG-600, so that the metal ions are embedded in the cross-linked network and the system is prevented from condensing, forming a cross-linked network with a large number of electrophilic sites (wherein lanthanum has a relatively high affinity for fluorine), and the substance can perform electrical neutralization, ion exchange, adsorption and capture with fluoride ions.
[0022] The present invention uses sodium carbonate solution for solidification, which is cheap; sodium carbonate has weaker alkalinity than sodium hydroxide and will not cause excessive re-dissolution of aluminum salt and lanthanum salt, and is less polluting than ammonia water.
[0023] The present invention adopts a vacuum freeze-drying method, which can fix free water. The volatilization rate is slow during freeze-drying, and the pore structure existing when the free water evaporates is retained, which can improve the adsorption capacity of the defluorinating agent.
[0024] In summary, this material has multiple functions such as electrical neutralization, ion exchange, adsorption capture, and pore adsorption, which make it have excellent adsorption and fluorine removal effect, and the material is environmentally friendly and safe.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The adsorption-type defluoridation agent of the present invention has multiple types of effects and achieves deep defluoridation, which can remove fluorine to below 0.2 ppm.
[0027] (2) The adsorption capacity of the adsorption-type defluorinating agent of the present invention can be as high as 480 mg / g. At the same time, the regeneration is simple, and only needs to be backwashed with 2% sodium carbonate solution. The regeneration efficiency can reach more than 96%. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] (1) Under stirring, 145 mL of 0.3 mol / L sodium silicate solution was slowly added to 100 mL of 10% hydrochloric acid aqueous solution, and the pH was measured to be 4.02.
[0031] (2) gradually adding 0.5% water-soluble chitosan (deacetylation degree>85%), stirring to dissolve, and reacting for 1 hour to obtain modified polysilicic acid.
[0032] (3) Add 0.2% PEG-4000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:2:1.5:0.5 gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution.
[0033] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into 500 mL of 10% mass concentration sodium carbonate solution and soak for 24 hours.
[0034] (5) Rinse with pure water, control the surface moisture, put it into the freezer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -50°C for lyophilization for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0035] Example 2
[0036] (1) Under stirring, 110 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 15% hydrochloric acid aqueous solution, and the pH was measured to be 3.68.
[0037] (2) gradually adding 1% water-soluble chitosan (90% deacetylation degree), stirring to dissolve, and reacting for 2 hours to obtain modified polysilicic acid.
[0038] (3) Add 0.7% PEG-2000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1.5:0.6 Gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain modified polysilicate aluminum magnesium lanthanum mixed solution.
[0039] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into 500 mL of 15% mass concentration sodium carbonate solution and soak for 24 hours.
[0040] (5) Rinse with pure water, control the surface moisture, first put it into the freezer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -60°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0041] Example 3
[0042] (1) Under stirring, 170 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.42.
[0043] (2) Gradually add 2% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0044] (3) Add 1.2% PEG-600 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8 gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain modified polysilicate aluminum magnesium lanthanum mixed solution.
[0045] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into 500 mL of 20% mass concentration sodium carbonate solution and soak for 24 hours.
[0046] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0047] Example 4
[0048] (1) Under stirring, 145 mL of 0.8 mol / L sodium silicate solution was slowly added to 100 mL of 25% hydrochloric acid aqueous solution, and the pH was measured to be 4.72.
[0049] (2) Gradually add 2.5% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 3 hours to obtain modified polysilicic acid.
[0050] (3) Add 1.7% PEG-400 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8 gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain modified polysilicate aluminum magnesium lanthanum mixed solution.
[0051] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into 500 mL of 25% mass concentration sodium carbonate solution and soak for 24 hours.
[0052] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0053] Example 5
[0054] (1) Under stirring, 170 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.42.
[0055] (2) gradually adding 3% water-soluble chitosan (90% deacetylation degree), stirring to dissolve, and reacting for 2 hours to obtain modified polysilicic acid.
[0056] (3) Add 2% PEG-600 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8 gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain modified polysilicate aluminum magnesium lanthanum mixed solution.
[0057] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into 500 mL of 25% mass concentration sodium carbonate solution and soak for 24 hours.
[0058] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0059] In order to highlight the beneficial effects of the present invention, the following comparative example experiments are given.
[0060] Comparative Example 1
[0061] (1) Under stirring, 170 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.45.
[0062] (2) 2% chitosan (55% deacetylation degree) was gradually added. It was difficult to dissolve under stirring at room temperature and had a high viscosity, so the next step of the reaction could not be carried out.
[0063] Comparative Example 2
[0064] (1) Under stirring, 170 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.4.
[0065] (2) According to n (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8 gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain polysilicate aluminum magnesium lanthanum solution.
[0066] (3) Add the modified polysilicate aluminum magnesium lanthanum solution dropwise into 500 mL of 20% mass concentration sodium carbonate solution and soak for 24 hours.
[0067] (4) Rinse with pure water, control the surface moisture, first put it into the freezer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for lyophilization for 24 hours. The obtained polysilicon aluminum magnesium lanthanum is in powder form.
[0068] Comparative Example 3
[0069] (1) Under stirring, 175 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.46.
[0070] (2) Gradually add 2% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0071] (3) According to n (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, aluminum salt, magnesium salt and lanthanum salt are gradually added, and the modified polysilicate aluminum magnesium lanthanum mixed solution obtained is in the form of gel agglomerates.
[0072] Comparative Example 4
[0073] (1) Under stirring, 165 mL of 0.5 mol / L sodium silicate solution was slowly added to 100 mL of 20% hydrochloric acid aqueous solution, and the pH was measured to be 3.4.
[0074] (2) Gradually add 2% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0075] (3) Add 1.2% PEG-20000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8 gradually add aluminum salt, magnesium salt and lanthanum salt, stir thoroughly and evenly to obtain a relatively viscous modified polysilicate aluminum magnesium lanthanum mixed liquid.
[0076] (4) The modified polysilicate aluminum magnesium lanthanum mixed solution was added dropwise into 500 mL of 20% mass concentration sodium carbonate solution. Due to the high viscosity, the particles dropped out were relatively large. The mixture was soaked for 24 hours.
[0077] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0078] The adsorption-type defluoridating agents prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests on defluoridation rate, adsorption capacity and regeneration efficiency for fluoride-containing water samples of different concentrations. The test method was based on GB / T 7484-1987 "Determination of fluoride in water - Ion-selective electrode method". The final calculation results are listed in Tables 1 and 2; Table 1 is a test for an aqueous solution with a fluoride content of 5 mg / L, and Table 2 is a test for an aqueous solution with a fluoride content of 20 mg / L.
[0079] Table 1 Fluoride removal rate of aqueous solution with fluoride content of 5 mg / L
[0080]
[0081] Table 2 Fluoride removal rate of aqueous solution with fluoride content of 20 mg / L
[0082]
[0083] It can be seen from the data in Table 1-2 that the adsorption-type defluoridation agent prepared in Examples 1-5 has significantly improved fluorine removal rate, adsorption capacity and regeneration efficiency compared with Comparative Examples 1-4, especially for water samples with high fluorine content, the adsorption-type defluoridation agent of the present invention has a more excellent effect.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an adsorption-type defluorinating agent, characterized in that: The following steps are involved: (1) Slowly adding sodium silicate solution to the hydrochloric acid aqueous solution under stirring to control the pH value to 3-5; (2) gradually adding polyhydroxyl high molecular weight organic matter, stirring and dissolving, and reacting for 1 to 3 hours to obtain modified polysilicic acid; (3) adding a water-soluble dispersant to the modified polysilicic acid, and then gradually adding aluminum salt, magnesium salt, and lanthanum salt, and stirring well to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution; (4) adding the modified polysilicate aluminum magnesium lanthanum mixed solution dropwise into the sodium carbonate solution and soaking for 12 to 24 hours; (5) washing with pure water, controlling the surface moisture, first placing it in the freezer layer of a refrigerator for pre-freezing, and then placing it in a vacuum freeze dryer for freeze-drying, thereby obtaining adsorption-type defluorination agent modified polysilicic acid aluminum magnesium lanthanum particles.
2. The method for preparing an adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (1), the mass fraction of the hydrochloric acid aqueous solution is 10% to 25%, and the concentration of the sodium silicate solution is 0.3 to 1 mol / L.
3. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (2), the polyhydroxy polymer organic substance is one or more of water-soluble chitosan, sodium carboxymethyl cellulose, sodium alginate, pectin, and polyvinyl alcohol.
4. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (2), the amount of polyhydroxy macromolecular organic matter added is 0.5% to 3%.
5. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (3), the dispersant is one or more of polyethylene glycol, lignin sulfonate, polyethylene imine, and dodecyl dimethyl betaine; wherein the average molecular weight of the polyethylene glycol is 400 to 4000; and the added amount of the dispersant is 0.2% to 2%.
6. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (3), n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2.5:0.5~1.5:0.3~0.
8.
7. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (4), the mass concentration of sodium carbonate is 10% to 25%.
8. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (5), the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 12 to 24 hours.
9. An adsorption-type defluorinating agent obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the adsorption-type defluoridating agent according to claim 9 in the treatment of fluorine-containing wastewater.
Citation Information
Cited By
Fluorine-containing wastewater treatment agent and preparation method thereof
CN121342140A
Fluorine-containing wastewater treatment agent and method for preparing the same
CN121342140B